2013
DOI: 10.4161/pri.26414
|View full text |Cite
|
Sign up to set email alerts
|

Life cycle of cytosolic prions

Abstract: Prions are self-templating protein aggregates that were originally identified as the causative agent of prion diseases in mammals, but have since been discovered in other kingdoms. Mammalian prions represent a unique class of infectious agents that are composed of misfolded prion protein. Prion proteins usually exist as soluble proteins but can refold and assemble into highly ordered, self-propagating prion polymers. The prion concept is also applicable to a growing number of non-Mendelian elements of inherita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 109 publications
0
11
0
Order By: Relevance
“…In direct coculture experiments, we have previously demonstrated coaggregation of induced NM-GFP aggregates in recipient NM-GFP sol cells with internalized HA-tagged NM from donor NM-HA agg cells ( 26 , 27 ). Of note, coaggregation of microscopically visible donor and recipient NM was a rare event during direct cell contact ( 26 , 27 ), indicating that smaller oligomers might also act as seeds. So far, we did not observe any coaggregation of internalized NM-HA seeds and induced NM-GFP aggregates after the addition of exosomes to recipient cells.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In direct coculture experiments, we have previously demonstrated coaggregation of induced NM-GFP aggregates in recipient NM-GFP sol cells with internalized HA-tagged NM from donor NM-HA agg cells ( 26 , 27 ). Of note, coaggregation of microscopically visible donor and recipient NM was a rare event during direct cell contact ( 26 , 27 ), indicating that smaller oligomers might also act as seeds. So far, we did not observe any coaggregation of internalized NM-HA seeds and induced NM-GFP aggregates after the addition of exosomes to recipient cells.…”
Section: Discussionmentioning
confidence: 98%
“…Cytosolic NM prion induction by direct cell-cell contact depends on the transfer of NM aggregates that seed the aggregation of soluble NM in the recipient cell ( 26 , 27 ). The exact size of the biologically active NM-HA seed is unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prions in lower eukaryotes are insoluble, self-perpetuating amyloid-like polymers that act as epigenetic elements of inheritance 9 . Unlike mammalian prions attached at the plasma membrane by a GPI-anchor, yeast prions are predominately cytoplasmic.…”
Section: Prions - Proteinaceous Infectious Particlesmentioning
confidence: 99%
“…While previous work revealed that metazoan cells exhibit disaggregation activity and also contain all co-factors required for cytosolic propagation and dissemination of an ectopically expressed amyloid-like yeast prion (Cohen et al, 2006; Hofmann and Vorberg, 2013; Hofmann et al, 2013; Krammer et al, 2009a; Krammer et al, 2009b), the nature of these co-factor(s) was still unclear, since direct homologs of HPS104 are absent from the metazoan cytosol. The recent discovery of a metazoan disaggregation machinery in which a particular HSP110-type nucleotide exchange factor (NEF) cooperates with the human HSP70-DNAJ system to fragment and depolymerize amyloid aggregates (Gao et al, 2015; Scior et al, 2018) has raised the question of whether this activity could prevent or promote the prion-like propagation of amyloid-type aggregates in metazoans and what physiological implications this would have.…”
Section: Introductionmentioning
confidence: 99%